Dune Development Dominates Flow Resistance Increase in a Large Dammed River - Yong Hu; Dongfeng Li; Jinyun Deng; Yao Yue; Junxiong Zhou; Chunrui Yang; Ninghui Zheng; Yitian Li (Water Resources Research)
Abstract Dunes are important for bedload transport in almost all large river systems and exert an important control flow resistance. Investigating dunes is fundamental for simulating discharge, sediment transport, and flood routing. However, the spatiotemporal dynamics of dunes and flow resistance remain poorly understood in large alluvial river systems mainly due to the lack of high‐resolution data. Here we analyzed in‐field observed data on annual profiles of 450 cross‐sections, river bathymetry, discharge, water levels, and sediment in the Middle Yangtze River, and found that dunes developed and flow resistance increased (+10%) in the post‐Three Gorges Dam period. We ascertain that the development of dunes plays the dominant role in augmenting flow resistance, as evidenced by roughness height change (+29%) using a modified Van Rijn method. Ultimately, dune development was incorporated into a hydrogeomorphic numerical model of the Yangtze River to improve flow resistance quantification, and thus, the water level simulation. Our findings highlight the potential increase in flow resistance in response to upstream damming in large rivers and have important implications for flood management and riverine ecology.